2018
DOI: 10.1097/wnf.0000000000000258
|View full text |Cite
|
Sign up to set email alerts
|

Anger Assessment in Patients Treated With Brivaracetam

Abstract: This small, open study suggests that BRV increases anger measures less than LEV in epilepsy patients. However, larger, blinded control studies are required to establish whether this apparent difference can be confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…The prospective design and objective evaluation of the anger levels are the main differential factors of this research. In line with previous literature, the results basically show that in an overall group of patients, which includes focal onset and idiopathic generalized epilepsies, BRV can be well tolerated with regard to drug-related irritability [13,[15][16][17]. However, seizure control in patients treated with BRV seems to be relevant to improve anger levels.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The prospective design and objective evaluation of the anger levels are the main differential factors of this research. In line with previous literature, the results basically show that in an overall group of patients, which includes focal onset and idiopathic generalized epilepsies, BRV can be well tolerated with regard to drug-related irritability [13,[15][16][17]. However, seizure control in patients treated with BRV seems to be relevant to improve anger levels.…”
Section: Discussionsupporting
confidence: 89%
“…Even in the presence of a psychiatric background or history of LEV-related adverse events, BRV can be safely used and is an effective AED alternative [13,20]. In a previous publication by our group independent from this study, we observed similar anger levels in BRV patients to other AEDs, and lower than those exposed to LEV [17]. Unlike some previous studies, we did not include patients with active psychiatric comorbidities and, therefore, we could not assess the antiaggression or mood stabiliser effects of BRV in that population setting [13].…”
Section: Discussionsupporting
confidence: 74%
“…LEV, PER, and TPM are associated with the highest reported frequency of AB among AEDs, particularly in patients with a previous history of psychiatric symptoms [4, 20, 21]. The recently introduced BRV, which is chemically closely related to LEV, is said to have less potential to induce behavioral side effects than LEV [6, 22, 23]. However, no studies that directly compare LEV and BRV have been published.…”
Section: Aggressive Behavior As An Adverse Effect Of Aedsmentioning
confidence: 99%
“…The broad pharmacological effect of LEV makes it difficult to determine the exact cause of AB. The high rate of AB with LEV may not necessarily be related to SV2A, since it has been suggested that BRV, which has a 15–30 times higher affinity to SV2A than LEV, is associated with a lower incidence of AB than LEV [6, 22, 23, 95]. Interestingly, it seems that BRV does not modulate NMDA, AMPA, or kainate receptors [96, 97].…”
Section: Possible Neuropharmacological Mechanisms Of Aed-induced Amentioning
confidence: 99%
“…It seems that BRV provides a more favorable neuropsychiatric safety profile than LEV [3] , [4] . Numerous studies have assessed the effect of this switch [4] , [5] , [6] , [7] , [8] , [9] , sometimes by means of an overlapping period of the two drugs. An overnight switch may improve therapeutic adherence and minimize AEs [10] .…”
Section: Introductionmentioning
confidence: 99%